228k views
4 votes
Solve the system by substitution

Solve the system by substitution-example-1
User Mavili
by
7.7k points

1 Answer

1 vote

Answer:

(x, y, z) = (-3, 2, 5)

Explanation:

Using the first equation, we can write an expression for x:

x = 21 +3y -6z

Substituting this into the remaining two equations gives ...

3(21 +3y -6z) +2y -5z = -30

63 +9y -18z +2y -5z = -30

11y -23z = -93

and

2(21 +3y -6z) -5y +2z = -6

42 +6y -12z -5y +2z = -6

y -10z = -48

This second equation makes it easy to write an expression for y:

y = 10z -48

Substituting that into the previous equation, we have ...

11(10z -48) -23z = -93

110z -528 -23z = -93

87z = 435

z = 5

y = 10(5) -48 = 2

x = 21 +3(2) -6(5) = -3

The solution is (x, y, z) = (-3, 2, 5).

User AgeDeO
by
8.4k points